Synthesis, physico-mechanical properties, material processing, and math models of novel superior materials doped flake of carbon and colloid flake of carbon - Kirgiz, Mehmet Serkan; Galdino, Andre Gustavo de Sousa; Kinuthia, John; Khitab, Anwar; Ul Hassan, Muhammad Irfan; Khatib, Jamal; Tiwary, Chandra Sekhar; Kırgız, Mehmet Serkan (Elsevier, 2021)
High performance colloid flake of carbon is gaining interest due importance in meeting the challenges of the globe. To make novel superior materials, the pulverized fuel ash-green adhesive based construction materials modified with the flake of carbon and the colloid flake of carbon were evaluated in view of synthesis, physico-mechanical properties, and material processing and models. For better understanding, such experimental samples as green adhesive plaster and green adhesive grout were made of the pulverized fuel ash of class C, the common adhesive, the flake of carbon, the colloid flake of carbon, fine sand, and the distilled water to compare with the structural material properties each other. The results of the adsorption spectra of optical atomic spectroscopy of the colloid flake carbon, the thickening-period of plaster, the spread and the consolidating level, the apparent unit volume mass, the apparent porosity, the apparent compacity, and the compressive stress of green grouts were reported in the research. It was concluded that the flake of carbon and the colloid flake of carbon led to important progress in the novel superior materials, e.g., accelerating of the thickening-period of plasters and increasing of the compressive stress of grouts. (c) 2021 The Author(s). Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: Flake of nano carbon; Colloid flake of carbon; Pulverized fuel ash; Mechanical properties; Physical properties; Durability; MECHANICAL-PROPERTIES; FLY-ASH; WASTE; GRAPHITE; CONCRETE; MICROSTRUCTURE; PERFORMANCE; COMPOSITES; MORTAR; CEMENT